Analysis of the effectiveness of long distance passes in 2014 Brazil FIFA World Cup - Marcos Antônio Mattos dos Reis; Fabrício Vieira do Amaral Vasconcellos; Marcos Bezerra de Almeida (Universidade Federal de Santa Catarina, 2017)
The aim of this study was to analyze the effectiveness of long distance passes performed during the 2014 Brazil FIFA World Cup. All 64 matches were analyzed, however, actions performed during overtime were not included in the sample. The study defined long pass as an action made by a player from the defensive midfield aiming at passing the ball to another teammate located on the offensive field. The action result assessment followed these criteria: shots on goal, ball possession maintenance, loss of ball possession and ball possession recovery. Total long distance passes were also considered in the analysis. Throughout the tournament, 4,512 long distance passes were attempted. The main findings were that 59% resulted on loss, 28% on maintenance and 12% on recovery of the ball possession, but only less than 1% resulted in shots on goal (F = 505.5; p<0.001; partial ƞ² = 0.76). Teams with the highest number of long pass attempts loose ball possession more frequently. There were more long distance passes at the first and at the last 15 min of matches. UEFA and Concacaf teams executed, respectively, the lowest and the highest number of long passes. The major outcome of this study is that long distance passes have low effectiveness due to the high rate of loss of ball possession, rarely creating score opportunities. The more the teams executed long passes, the more the teams lose ball possession.